Prediction of diabetes with hybrid prediction model us-ing big data in health care - Rama Kalaivani, E.; Ramesh Marivendhan, E.; Suma, N. (International Journal of Engineering and Technology, 2017)
Technology is advancing in healthcare to comply with unique regulatory guidelines designed to support public safety. The realistic way of Big Data can unify all patient related data to get a 360-degree view of the patient to analyze and predict outcomes. Big Data is a buzzword which is reigning the innovation market from quiet sometime and trends which can give birth to new line of treatment of diseases and provide high quality healthcare at lower cost to all. These issues include benefits of Big Data, its applications and opportunities in medical areas and health care. This paper includes the basics of big data, clinical prediction model for predicting whether the diagnosed patient suffers from diabetes. Hybrid prediction model is chosen and it is used to predict the disease.